2022
DOI: 10.3390/bios12080558
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Small and Metabolizable Near-Infrared Au/Gd Nanoclusters for Targeted FL/MRI Imaging and Cancer Theranostics

Abstract: Tumor accurate imaging can effectively guide tumor resection and accurate follow-up targeted therapy. The development of imaging-stable, safe, and metabolizable contrast agents is key to accurate tumor imaging. Herein, ultra-small and metabolizable dual-mode imaging probe Au/Gd@FA NCs is rationally engineered by a simple hydrothermal method to achieve accurate FL/MRI imaging of tumors. The probes exhibit ultra-small size (2.5–3.0 nm), near-infrared fluorescence (690 nm), high quantum yield (4.4%), and a better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…At room temperature, a mixture of ethanol (18 mL), TEO (6 mL), and GdCl 3 ·6H 2 O aqueous solution (5 wt %, 20 mL) (with a Au-to-Gd mass ratio of 1:1) and an NH 4 OH solution containing 25% NH 3 (9 mL) were continuously stirred at 1500 rpm. TEOS and GdCl 3 were added to prepare the Gd-SiO 2 nanoshell, with a dropwise rate controlled at 20 drops/s and stirred for 1 h. The obtained silica colloid was aged for 1 day. Au@Gd-SiO 2 nanoparticles underwent multiple centrifugation and washing steps to remove unreacted CTAB, GdCl 3 , and TEOS. Au@Gd-SiO 2 (200 mg) was dispersed in a solution containing concentrated hydrochloric acid (60 μL, 37%) and ethanol (30 mL).…”
Section: Methodsmentioning
confidence: 99%
“…At room temperature, a mixture of ethanol (18 mL), TEO (6 mL), and GdCl 3 ·6H 2 O aqueous solution (5 wt %, 20 mL) (with a Au-to-Gd mass ratio of 1:1) and an NH 4 OH solution containing 25% NH 3 (9 mL) were continuously stirred at 1500 rpm. TEOS and GdCl 3 were added to prepare the Gd-SiO 2 nanoshell, with a dropwise rate controlled at 20 drops/s and stirred for 1 h. The obtained silica colloid was aged for 1 day. Au@Gd-SiO 2 nanoparticles underwent multiple centrifugation and washing steps to remove unreacted CTAB, GdCl 3 , and TEOS. Au@Gd-SiO 2 (200 mg) was dispersed in a solution containing concentrated hydrochloric acid (60 μL, 37%) and ethanol (30 mL).…”
Section: Methodsmentioning
confidence: 99%
“…Gold nanoclusters (Au NCs) have the advantages of easy preparation and modification, high biocompatibility, stable fluorescence (FL) performance, and easy assembly with other functional nanomaterials. They have been extensively implemented in biological imaging, drug delivery, targeted therapy, and the construction of multifunctional therapeutic nanoplatforms. Several studies have demonstrated the potential of Au NCs to achieve synergistic therapeutic effects with other materials. For example, Yang et al reported a novel bionanosystem by combining glutathione capped Au NCs with two-level mesoporous canal silica, which not only enhanced the FL intensity but also achieved the synergistic therapeutic effects of PTT and PDT .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] In addition, folate receptors (FRs) are considered a potential target for cancer therapeutics because they are overexpressed in many cancer cells. [30][31][32][33] For example, SW1990 pancreatic cancer cells highly express FRs and could be the subject of research targeting pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%